Impact of leaflet-to-annulus index on residual tricuspid regurgitation following transcatheter edge-to-edge tricuspid valve repair. (14th October 2021) - Tanaka, T; Sugiura, A; Kavsur, R; Vogelhuber, J; Oeztuerk, C; Becher, M U; Zimmer, S; Nickenig, G; Weber, M
Abstract: Introduction: Edge-to-edge transcatheter tricuspid valve repair (TTVR) is a promising treatment option for tricuspid regurgitation (TR), and it is required to identify anatomical parameters to predict the procedural success of TTVR. Purpose: In this study, we assessed leaflet-to-annulus index (LAI), a simple tool to evaluate the remodeling of tricuspid annulus in relation to the leaflets, and investigated the association of the LAI with residual TR after edge-to-edge TTVR. Methods: Consecutive 140 patients with symptomatic TR who underwent edge-to-edge TTVR from June 2015 to July 2020 were enrolled. The LAI was calculated using preprocedural transesophageal echocardiography and was defined as follows: (anterior leaflet length + septal leaflet length)/anteroseptal tricuspid annulus diameter (Figure 1). Primary outcome was residual TR ≥3+ at discharge, and patients were allocated into two groups as follows: residual TR ≥3+ and <3+. Secondary outcome was the composite outcome, consisting of all-cause mortality and heart failure hospitalization, within one year after TTVR. Results: Of the 140 patients, 43 patients had residual TR ≥3+ after TTVR. The patients with residual TR ≥3+ had lower LAI compared to those with residual TR <3+ (1.06±0.10 vs. 1.13±0.09; p=0.001). Multivariable analysis revealed that LAI was associated with residual TR ≥3+ (odds ratio [by 0.1 increase]: 0.57; 95% confidence interval [95% CI]: 0.35–0.94; p=0.02), independently of baseline TR severity, location of TR jet, and coaptation gap size (Table 1). Patients with residual TR ≥3+ had a higher incidence of the composite outcome within one year after TTVR (34.9% vs. 18.6%; log-rank p=0.04) and residual TR ≥3+ was an independent predictor of the composite outcome within one year (hazard ratio: 2.04; 95% CI: 1.01–4.11; p=0.04). Conclusion: Lower LAI is associated with residual TR ≥3+ after edge-to-edge TTVR, which itself was a significant predictor of the one-year composite outcome. Our findings suggest that LAI is a useful tool to identify patients to be successfully treated with edge-to-edge TTVR. FUNDunding Acknowledgement: Type of funding sources: None.